Ecuador’s fiscal policy and the impact of exogenus shocks on economic growth (2012-2023) - Salvador, Juan Carlos (2023)
This article analyzes the relationship between public spending on current payroll, consumer goods and services, investment in non-financial assets (IANF), value-added and income taxes, as instruments of fiscal policy, on Gross Domestic Product (GDP) for the period 2012-2023q1. The time series approach is used with the application of the SVAR Model following the proposals developed by Blanchard and Perotti (1999) and Perotti (2004) to calculate the fiscal multipliers expressed as Cumulative Impulse Response Function. The results provide evidence that expansionary fiscal shocks on the payroll have positive effects in the short term, however the fiscal multiplier is lower in relation to the IANF, while in the income tax it is higher in relation to the Value-added tax.